Landscape, form and process: some implications for San rock art research - Solomon, A. (Southern African Humanities, 2021)
A current trend in South African (and other) rock art research has been to focus on formal analysis, as well as the traditional iconographical studies, which are concerned primarily with descriptions of 'subject matter', and with the function of imagery. Recent anthropological and archaeological work, such as that of Ingold, has highlighted the notion of 'landscape' as a means of moving beyond structuralist and functionalist analyses. The approachis adapted here in order to consider the relatively rare portrayal of features of the physical environment by San artists. Rock paintings from KwaZulu-Natal and the south-western Cape are discussed in a preliminary attempt to illustrate the utility of the approach. To cite this paper: Solomon, A. 1997. Landscape, form and process: some implications for San rock art research. Natal Museum Journal of Humanities 9: 57-73.